A multicenter study to evaluate pulmonary function in osteogenesis imperfecta. Issue 6 (24th September 2018) - Tam, Allison; Chen, Shan; Schauer, Evan; Grafe, Ingo; Bandi, Venkata; Shapiro, Jay R.; Steiner, Robert D.; Smith, Peter A.; Bober, Michael B.; Hart, Tracy; Cuthbertson, David; Krischer, Jeffrey; et al.
Abstract : Pulmonary complications are a significant cause for morbidity and mortality in osteogenesis imperfecta (OI). However, to date, there have been few studies that have systematically evaluated pulmonary function in individuals with OI. We analyzed spirometry measurements, including forced vital capacity (FVC) and forced expiratory volume in the first second (FEV1 ), in a large cohort of individuals with OI (n = 217) enrolled in a multicenter, observational study. We show that individuals with the more severe form of the disease, OI type III, have significantly reduced FVC and FEV1 which do not follow the expected trends of the normal population. We also show that "normalization" of FVC and FEV1 using general population data to generate percent predicted values underestimates the pulmonary involvement in OI. Within each subtype of OI, we used linear mixed models to find potential correlations between FEV1 and FVC with the clinical variables including mobility, bisphosphonate use, and scoliosis. Our results are an important step in understanding the extent of pulmonary involvement in individuals with OI and for developing pulmonary endpoints for use in the routine patient care as well as in the investigation of new therapies. Abstract : Forced vital capacity (FVC) and forced expiratory volume in the first second (FEV1 ) were significantly reduced in type III osteogenesis imperfecta (OI).